Uglies. Shay's story - Westerfeld, Scott; Grayson, Devin K. (Del Rey/Ballantine Books, 2012)
Shay awaits the time when she will go through a rite-of-passage operation that transforms ordinary Uglies into Pretties. However, after she becomes involved with the Crims, a rebellious group of teens who venture outside of the borders of Uglyville, she begins to question the whole concept of being a Pretty.